Conference Possibilities and Limits of Research of the History of College Education after 1945.: October 14-5, 2009, Hradec Králové, Czech Republic. - Soukupová, Blanka (Lidé města, 2010)
The above-mentioned conference was devoted to colleges which are typical urban institutions. And it was and is also a college educational system for which cities are considered to be centers of cultural life and focal points of innovation. On the other hand, universities often changed into fuses of conflict, or in them is concentrated form of loyalty to totalitatian regime aroses.